Salt hydrate phase change materials: current state of art and the road ahead - Dixit, Prakhar (2022)
Due to high energy storage densities and reduced requirement of maintenance or moving parts, phase change materials are believed to have great potential as thermal energy storage materials. Salt hydrate phase change materials have been relevant since the earliest commercial deployment of latent heat thermal energy storage solutions, however a deeper look into the present standing, commercial requirements and performance improvements of this class of materials indicates that their capabilities have remained underdeveloped, and their advantages, underleveraged. These phase change materials have better thermal performance, better flame retardance, lower manufacturing costs, and a more sustainable supply than their organic counterparts, although a few limitations still exist, often hampering a more widespread adoption. As such, much research in recent years has been focused on eliminating these shortcomings. Presently, all these challenges are critically reviewed, and relevant mitigation/enhancement strategies are also discussed. In the purview of this discussion, shape stabilized composites arise as a singular strategy to alleviate the performance properties of salt hydrate phase change materials across multiple dimensions. A detailed review on the advantages offered by shape stabilized phase change materials is presented along with relevant development studies reported in the literature. Altogether, the reported information provides a perspective towards commercial realization of salt hydrate phase change materials in a wide range of applications, spanning from cold chain logistics to textile incorporation and building materials to solar heating solutions.